Pendampingan Orang Tua terhadap Pendidikan Anak di Era Digital Desa Sugihwaras kecamatan Sugihwaras kabupaten Bojonegoro - Aziz, Maskur; Rofi'ah, Risatur; Zahra, Aprilia; Murdhiyatun, Siti Nur (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
The research in this perenting seminar includes parental assistance in assisting children's education in the digital era which was carried out at SDN 3 Sugihwaras, Sugihwaras district, Bojonegoro district. In this study, the ABCD (Asset Based Community Development) method is used which is a special approach by developing assets that already exist in the community itself, in addition to the ABCD method, the author also uses a descriptive method. The purpose of this study is to find out the right way to assist parents in supervising children's education in the digital era, which is the main problem for students in today's digital era. From this research, it was obtained that good assistance in the digital era must be adjusted according to the needs and characteristics of children, where each child has their own specialties.